Moral Education in Malaysian Islamic Boarding Schools: Challenges Faced by Educators in Nurturing Ethical Imitation - Fahmi Irfani; Makbula, Muhamad Hajan; Fariduddin, Ecep Ishak; Aly, Fahmi (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
Moral education constitutes a cornerstone of holistic student development within Islamic boarding schools in Malaysia, where the cultivation of values and character is viewed as integral to academic achievement. Among the pedagogical strategies employed, ethical imitation, encouraging students to emulate the behavior and values of their teachers, emerges as a central approach. Despite its significance, the consistent implementation of this method presents a series of challenges for educators. The present study aims to examine these obstacles by focusing on both structural and personal dimensions that influence moral pedagogy. Using a qualitative design, data were collected through semi-structured interviews with teachers and direct classroom observations across several selected boarding schools. The findings reveal four prominent barriers: inconsistency in student behavior, insufficient parental engagement, the influence of broader socio-cultural dynamics, and teachers’ own difficulties in maintaining exemplary moral conduct under demanding circumstances. These challenges not only undermine the effectiveness of moral imitation but also highlight the complexity of cultivating moral integrity in contemporary educational settings. The study emphasizes the need for continuous professional development, stronger institutional frameworks, and a collaborative moral ecosystem that actively involves parents, teachers, and the wider school community. By situating these insights within the broader discourse on Islamic education, the research offers practical recommendations for enhancing character-building initiatives and advancing sustainable models of moral pedagogy in Malaysian boarding schools.